PELATIHAN PELAYANAN ADMINISTRASI PERKANTORAN MENUJU GAMPONG YANG GOOD GOVERNANCE DI GAMPONG KEUDE JRAT MANYANG KECAMATAN TANAH PASIR KABUPATEN ACEH UTARA - Bobby Rahman; M Akmal; Rasyidin Rasyidin; Teuku Muzaffarsyah; Zulhilmi Zulhilmi; Dahlan A Rahman (Indonesian Community Service and Empowerment Journal (IComSE), 2022)
The process of administrative services is also less obtained by the community today due to a lack of understanding of technical services by the apparatus in gampong government offices. Service patterns that have not been well organized coupled with the unsanciplined service pattern add dull to the face of service in Gampong Jrat Manyang. This service presents several problem points that arise from partners, namely Gampong Administrative Services that have not been efficient so that basic training of administrative services is needed.. The method of implementation of pre-implementation of activities requires observation of the location of the devotion so that the criteria are obtained that become the basis of community assessment of services such as Tangible. The results showed the core apparatus was very large reaching 60 percent of the total 100 percent. So this percentage shows the interest of gampong government administrators Keude Jrat Manyang as trainees and they are aware that the administrative services carried out so far from efficient. Key words: service, administration, gampong, good governance